Optimization of Energy Consumption in Net-Zero Energy Buildings with Increasing Thermal Comfort of Occupants - Mohsen Mahdavi Adeli; Said Farahat; Faramarz Sarhaddi (International Journal of Photoenergy)
Residential and commercial buildings consume approximately 60% of the world’s electricity. It is almost impossible to provide a general definition of thermal comfort, because the feeling of thermal comfort is affected by varying preferences and specific traits of the population living in different climate zones. Considering that no studies have been conducted on thermal satisfaction of net-zero energy buildings prior to this date, one of the objectives of the present study is to draw a comparison between the thermal parameters for evaluation of thermal comfort of a net-zero energy building occupants. In so doing, the given building for this study is first optimized for the target parameters of thermal comfort and energy consumption, and, hence, a net-zero energy building is formed. Subsequent to obtaining the acceptable thermal comfort range, the computational analyses required to determine the temperature for thermal comfort are carried out using the Computational Fluid Dynamics (CFD) model. The findings of this study demonstrate that to reach net-zero energy buildings, solar energy alone is not able to supply the energy consumption of buildings and other types of energy should also be used. Furthermore, it is observed that optimum thermal comfort is achieved in moderate seasons.